GAMBARAN KINERJA KADER JUMANTIK DALAM PEMBERANTASAN SARANG NYAMUK DBD DI KECAMATAN PADANG HULU KOTA TEBING TINGGI TAHUN 2013 - arietha hutapea; Linda T Maas; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
ABSTRACT Dengue hemorrhagic fever (DHF) is an endemic disease in Tebing Tinggi. Based on Tebing Tinggi Health Department Profile in 2012, there were 150 dengue cases. To reduce morbidity and mortality of DHF, community participation is absolutely necessary to conduct mosquito eradication nest (PSN). Larva monitoring cadres (Jumantik) is one from of community participation in dengue prevention. Active jumantik expected to affect the decrease in morbidity and mortality due to dengue cases. Padang Hulu District is one of districts in Tebing Tinggi which has high dengue cases. This purpose of this research is to describe the Jumantik cadres performance in eradicate the mosquito nest in Padang Hulu District, Tebing Tinggi. This is a descriptive research with quantitative methodology approach with 78 respondents as the total samples. The respondence performance is measured on as the motivators, initiators, and facilitators, from all the result show of measurement are in the middle level, with the percentage motivators (60%), inistiators (56.4%) and facilitators (85.9%) The results of this research shows, most of the respondence by the age 20-34 years old (41%), female (94.9%), senior high school (88.5%) and house wife (85.9%).  From organization variables know perspective the performance of responden is measured by through the facilities, leadership and reward system and the result show of measurement are in the high level for facilities (65.4%) and leadershipment (60.3%) , middle level for reward system (73.1%).Psychological variables know perspective the performance of responden is measured by through the training are in the middle level (65.4%) and the motivation are in the high level (51.3%). In order to optimize they should be consideration the implementation, there are some consideration such as improving training, transport honorarium and completeness facilities.